Nominal group techniques to assess teachers’ readiness for online teaching at higher education institution - Mohd Nasir, Farah Damia; Nusantara, Toto; Ghazali, Norliza; Mustakim, Siti Salina; Anggraini, Ade Eka (Institute of Advanced Engineering and Science, 2024)
Education 4.0 marks a new era of learning with virtual online classrooms, requiring teachers to adapt. Despite this shift, standardized tools to evaluate teachers’ online instruction readiness are lacking. This article explores nominal group technique (NGT) in the design and development research (DDR) need analysis stage to identify challenges in online teaching and the need for a new assessment tool in higher education. There were 15 professionals from Malaysia and Indonesia contributed insights to identify key educator challenges. Results show validation of study topics with over 70% agreement, highlighting the urgent need for a reliable tool to assess educators’ online instruction competence in higher education. These findings inform further instrument development.